1989
DOI: 10.2307/2008479
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Filters for Efficient Shock Computation

Abstract: Abstract.A new type of methods for the numerical approximation of hyperbolic conservation laws with discontinuous solution is introduced. The methods are based on standard finite difference schemes. The difference solution is processed with a nonlinear conservation form filter at every time level to eliminate spurious oscillations near shocks. It is proved that the filter can control the total variation of the solution and also produce sharp discrete shocks. The method is simpler and faster than many other hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…corrections are made to each extremum in the characteristics Equations (5) and (9) can be written in the form arrays according to the criteria given in Algorithm 4.1 in [5]. The only modification we made is in the size of the correction ͳ (discussed in the next section).…”
Section: The Engquist Filtermentioning
confidence: 99%
See 2 more Smart Citations
“…corrections are made to each extremum in the characteristics Equations (5) and (9) can be written in the form arrays according to the criteria given in Algorithm 4.1 in [5]. The only modification we made is in the size of the correction ͳ (discussed in the next section).…”
Section: The Engquist Filtermentioning
confidence: 99%
“…Afterward, the physical vari-ѨU Ѩt ϩ ѨF Ѩx ϭ Q (13) ables are calculated from the corrected characteristic variables. As mentioned in [5], because TVD is enforced in characteristics the quasilinear form of which is space, the physical variables may occasionally violate the TVD criterion. Indeed, in our numerical experiments, TVD is occasionally violated in the physical variables; however, the oscilla-…”
Section: The Engquist Filtermentioning
confidence: 99%
See 1 more Smart Citation
“…In practice the use of a blend of low-and high-order dissipative terms with adaptive coefficients conditioned to the maximum local wave speed can yield effective shock capturing schemes. Recently Engquist, Lotstedt, and Sjogreen have shown that oscillations can be effectively controlled by post-processing the result after each time step with a filter which is applied only if a new extremum is detected (31). These procedures lead to a set of coupled ordinary differential equations, which can be written in the form dw dt…”
Section: Algorithms For Flow Simulationmentioning
confidence: 99%
“…For that reason, filtering methodŝ were developed, beginning in the late eighties. The first one, described by B. Engquist and B. Sjogreen in [1], uses simple TVD and conservation properties to correct nonphysical spurious oscillations from one time step to another. The correction step consists in pushing numerical data points up or down to an acceptable level while preserving conservation.…”
Section: Introductionmentioning
confidence: 99%